Enhancing Sustainability in Packaging: Response Surface Optimized Sago Pith Waste Biocomposites with PBAT and MDI - Maya Irmayanti; Sarifah Nurjanah; Akbar Hanif Dawam Abdullah; Rossy Choerun Nissa; Yeyen Nurhamiyah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aims to optimize the biocomposites of sago pith waste (SPW) for sustainable packaging applications. The biocomposite was prepared using the biodegradable polymer polybutylene adipate-co-terephthalate (PBAT) as a matrix and methylendifenyl diisocyanate (MDI) as a chain extender. RSM-CCD was used to assess the impact of the incorporation of SPW (5-20% p/p) and MDI (1–5%) into the PBAT matrix on the tensile strength and elongation of biocomposites by melt mixing. The optimal formula shown by RSM was 5% SPW and 5% MDI, which resulted in a 5.14 MPa tensile strength and 8.14% elongation. The barrier properties of all treatments, including moisture content, contact angle, and water absorption, were checked. The optimal formula showed good barrier properties compared to other treatments: water content of 3.12%, contact angle of 42.84°, and water absorption of 0.82%. Other characterizations of SEM, FTIR, DSC, TGA, and biodegradability tests showed an increase in SPW-PBAT compatibility due to the use of MDI. MDI as a chain extender had a positive impact on the material's strength, and the addition of SPW accelerated the degradation process, thus improving biodegradability. Keywords: Biocomposite, Chain extender, Melt-mixing, Response Surface Methodology, Sago pith waste.